The THE USE OF MODULAR DISTANCE LEARNING IN RELATION TO THE PROBLEM-SOLVING SKILLS IN STATISTICS AND PROBABILITY OF GRADE 11 STUDENTS - QUIANO, MAILA; Beniegas Avila, Elda (International Journal of Business, Law, and Education, 2023)
This study determined the use of modular distance learning (MDL) in relation to the problem-solving skills in statistics and probability of Grade 11 students in Bula National High School, the School year 2021-2022. It drew out the profile of the Grade 11 learners’ pre-test scores of the problem-solving skills in Statistics and probability utilizing modular distance learning in terms of Analysis, Estimation and Approximation, Hypothesis Testing, and Applied math; the profile of the learners' post-test scores after their exposure to the modular distance learning; tested the significant change in the improvement brought by the utilization of MDL, and the uses of findings to apply in the lesson content and subject matter in Statistics and Probability. The study used the descriptive-evaluative correlational method to determine the data needed under the present investigation. Purposive and quota sampling was used. The research Subjects were the (30) Grade 11 learners of Bula National High School. Weighted Mean, frequency count, percentage, mean and MPL, and t-test were used to treat the data statistically. The significance level was set at 0.05. It revealed that the profile of the learners' post-test scores after their exposure to modular distance learning is satisfactory and significant improvement existed, implying that the utilization of modular distance learning in statistics and probability is effective.